Glioblastoma Stem Cells Microenvironment: The Paracrine Roles of the Niche in Drug and Radioresistance. (6th January 2016) - Fidoamore, Alessia; Cristiano, Loredana; Antonosante, Andrea; d'Angelo, Michele; Di Giacomo, Erica; Astarita, Carlo; Giordano, Antonio; Ippoliti, Rodolfo; Benedetti, Elisabetta; Cimini, Annamaria
Abstract : Among all solid tumors, the high-grade glioma appears to be the most vascularized one. In fact, "microvascular hyperplasia" is a hallmark of GBM. An altered vascular network determines irregular blood flow, so that tumor cells spread rapidly beyond the diffusion distance of oxygen in the tissue, with the consequent formation of hypoxic or anoxic areas, where the bulk of glioblastoma stem cells (GSCs) reside. The response to this event is the induction of angiogenesis, a process mediated by hypoxia inducible factors. However, this new capillary network is not efficient in maintaining a proper oxygen supply to the tumor mass, thereby causing an oxygen gradient within the neoplastic zone. This microenvironment helps GSCs to remain in a "quiescent" state preserving their potential to proliferate and differentiate, thus protecting them by the effects of chemo- and radiotherapy. Recent evidences suggest that responses of glioblastoma to standard therapies are determined by the microenvironment of the niche, where the GSCs reside, allowing a variety of mechanisms that contribute to the chemo- and radioresistance, by preserving GSCs. It is, therefore, crucial to investigate the components/factors of the niche in order to formulate new adjuvant therapies rendering more efficiently the gold standard therapies for this neoplasm.